T118N Substitution of Hepatitis B X Protein Reduces Colony Formation of HepG2 Cells - Artarini, Anita; Nurmalasari, Dewi Riskha; Permanasari, Silmi Citra; Riani, Catur; Tjandrawinata, Raymond Rubianto; Retnoningrum, Debbie Soefie (The Indonesian Biomedical Journal, 2023)
BACKGROUND: The acute Hepatitis B virus (HBV) infection usually ceases before six months, but chronic infection that lasts for more than six months might develop into liver cirrhosis and hepatocellular carcinoma (HCC). Viral particle load, HBV genotypes and association to the HBV x (HBx) gene mutations are the probable factors related to HCC occurrence. The mutation which leads to HBx T118N was found as the second most common HBx mutation in Indonesia, as compared to the known cancer-related HBx K130M/V131I mutant. However, the effect of T118N mutation and its combination with K130M/V131I on human hepatoma cells has not been elucidated well. Hence, this study was conducted to dissect the role of HBx T118N and its mutant combination in colony formation, as compared to the wild type HBx and cancer-related HBx K130M/V131I.METHODS: In this study, the genes encoding wild type HBx, HBx T118N, and HBx K130M/V131I mutations were obtained as synthetic gene. Meanwhile, the gene encoding HBx T118N/K130M/V131I mutations was successfully generated using site-directed mutagenesis. The optimum condition for colony formation assays was determined through Zeocin sensitivity test of HepG2 cells.RESULTS: Selection of HepG2 cells using Zeocin was determined at 200 µg/mL. Colony formation assays performed upon expression of HBx T118N and HBx T118N/K130M/V131I mutant proteins showed reduced colony numbers as compared to the expression of wild type HBx, similar to the effect from HBx K130M/V131I mutant expression.CONCLUSION: The HBx T118N and HBx T118N/K130M/V131I mutation caused less colony formation of HepG2 cells, similar to the K130/M131I mutation. This indicates a possible role of the T118N mutation in liver cancer development.KEYWORDS: colony formation assay, hepatitis B virus, HBx, T118N, K130M/V131I